Awareness and Precautions of University Students about Cyberbullying - Atyaf Raheem Mansour,; Ali Kareem Al-Juboori, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The phenomenon of cyberbullying emerged alongside the technological advancements with it numerous disadvantages, particularly at the academic level for students. Therefore, students' awareness of cyberbullying’s dangers contributes to their adoption of precautionary measures to protect themselves and efficiently handle cyberbullying incidents Objectives: The study aimed to examine the awareness and precautions of university students about cyberbullying Methods: A non-probability (convenience sample) of 450 students was selected from colleges of medicine ,nursing ,pharmacy and dentistry at University of Kerbala, Iraq, according to specific criteria. The data were collected through questionnaire by using the cyberbyllying awareness scale developed by Ayas, T., Aydın, F. & Horzum, M. B. (2015) and the precaution against cyberbullying scale developed by the authors. Data were analyzed through use application of Statistical Package for Social Sciences (SPSS.26). Results: students are highly aware of cyberbullying as reported by 71.1% of them (M±SD= 92.34±13.670) they also have good precautions to avoid cyberbullying as reported by 72.9% of them (M±SD= 50.77±6.376), in addition there is strong positive significant relationship between students’ precautions and their awareness about cyberbullying at p-values ≤ 0.001. Conclusion: the student's awareness of cyberbullying is crucial for building up precautionary measures in order to keep themselves safe and avoid any negative consequences while browsing the internet.